Graywater Treatment with Two Planted Vertical Constructed Wetlands in Series: A Pilot Study. Issue 9 (25th July 2022) - Hachicha, Rihab; Fersi, Mariem; Jedidi, Naceur; Mechichi, Taher; Hassen, Abdenaceur; Hachicha, Ridha
Abstract: Two pilot scales of planted vertical flow‐built wetlands in series treating greywater were accomplished in the Tunisian Deaf Help Association (TDHA). The two beds were planted with Phragmites australis with continuous daily flow of 640 L and nominal operating retention duration of 1.25 days. The total suspended solids (TSS) removal efficiency in the first bed was 86.2 ± 10%, and both beds received the same treatment performance for chemical oxygen demand (COD) and biochemical oxygen demand after five days (BOD5). The removal rates for TSS, COD, and BOD5 were 94 ± 13, 86 ± 5.7, and 93 ± 7%, respectively., the ammonium overall removal rate was 71.4 ± 19.1% in both beds, however, it was around 60 ± 9.11% when based on a single bed. The second bed enhanced phosphorus removal twice with a reduction of 52%. In each bed, Escherichia coli clearance ranged from 1.24 to 2.40 logs, respectively, and the total average bacteria population yielded an average of 1.65 log units, equivalent to an efficiency of 46.67%. These results were complemented by polymerase chain reaction‐denaturing gradient gel electrophoresis, showing an overall of biomass reduction of 47 ± 8% with one bed, and of 89 ± 7% with both beds. Abstract : Built wetland techniques have proven to be efficient in wastewater treatment and reuse. In this study two vertical flow beds in series are planted with Phragmites australis to treat graywater. Monitoring of sanitary indicator bacteria and chemical parameters such as total suspended solids, chemical and biochemical oxygen demand, and phosphorus and ammonium content shows good removal efficiency of the system.